diff -r b4472ebd7fad -r 619ecb57db38 Nominal/Nominal2_Abs.thy --- a/Nominal/Nominal2_Abs.thy Thu Jan 13 12:12:47 2011 +0000 +++ b/Nominal/Nominal2_Abs.thy Fri Jan 14 14:22:25 2011 +0000 @@ -545,17 +545,15 @@ lemma Abs_rename_set: fixes x::"'a::fs" - assumes a: "(p \ bs) \* (bs, x)" + assumes a: "(p \ bs) \* x" and b: "finite bs" shows "\q. [bs]set. x = [p \ bs]set. (q \ x) \ q \ bs = p \ bs" proof - - from a b have "p \ bs \ bs = {}" using at_fresh_star_inter by (auto simp add: fresh_star_Pair) - with set_renaming_perm - obtain q where *: "q \ bs = p \ bs" and **: "supp q \ bs \ (p \ bs)" using b by metis + from b set_renaming_perm + obtain q where *: "q \ bs = p \ bs" and **: "supp q \ bs \ (p \ bs)" by blast have "[bs]set. x = q \ ([bs]set. x)" apply(rule perm_supp_eq[symmetric]) using a ** - unfolding fresh_star_Pair unfolding Abs_fresh_star_iff unfolding fresh_star_def by auto @@ -566,17 +564,15 @@ lemma Abs_rename_res: fixes x::"'a::fs" - assumes a: "(p \ bs) \* (bs, x)" + assumes a: "(p \ bs) \* x" and b: "finite bs" shows "\q. [bs]res. x = [p \ bs]res. (q \ x) \ q \ bs = p \ bs" proof - - from a b have "p \ bs \ bs = {}" using at_fresh_star_inter by (simp add: fresh_star_Pair) - with set_renaming_perm - obtain q where *: "q \ bs = p \ bs" and **: "supp q \ bs \ (p \ bs)" using b by metis + from b set_renaming_perm + obtain q where *: "q \ bs = p \ bs" and **: "supp q \ bs \ (p \ bs)" by blast have "[bs]res. x = q \ ([bs]res. x)" apply(rule perm_supp_eq[symmetric]) using a ** - unfolding fresh_star_Pair unfolding Abs_fresh_star_iff unfolding fresh_star_def by auto @@ -587,17 +583,14 @@ lemma Abs_rename_lst: fixes x::"'a::fs" - assumes a: "(p \ (set bs)) \* (bs, x)" + assumes a: "(p \ (set bs)) \* x" shows "\q. [bs]lst. x = [p \ bs]lst. (q \ x) \ q \ bs = p \ bs" proof - - from a have "p \ (set bs) \ (set bs) = {}" using at_fresh_star_inter - by (simp add: fresh_star_Pair fresh_star_set) - with list_renaming_perm - obtain q where *: "q \ bs = p \ bs" and **: "supp q \ set bs \ (p \ set bs)" by metis + from a list_renaming_perm + obtain q where *: "q \ bs = p \ bs" and **: "supp q \ set bs \ (p \ set bs)" by blast have "[bs]lst. x = q \ ([bs]lst. x)" apply(rule perm_supp_eq[symmetric]) using a ** - unfolding fresh_star_Pair unfolding Abs_fresh_star_iff unfolding fresh_star_def by auto @@ -611,21 +604,21 @@ lemma Abs_rename_set': fixes x::"'a::fs" - assumes a: "(p \ bs) \* (bs, x)" + assumes a: "(p \ bs) \* x" and b: "finite bs" shows "\q. [bs]set. x = [q \ bs]set. (q \ x) \ q \ bs = p \ bs" using Abs_rename_set[OF a b] by metis lemma Abs_rename_res': fixes x::"'a::fs" - assumes a: "(p \ bs) \* (bs, x)" + assumes a: "(p \ bs) \* x" and b: "finite bs" shows "\q. [bs]res. x = [q \ bs]res. (q \ x) \ q \ bs = p \ bs" using Abs_rename_res[OF a b] by metis lemma Abs_rename_lst': fixes x::"'a::fs" - assumes a: "(p \ (set bs)) \* (bs, x)" + assumes a: "(p \ (set bs)) \* x" shows "\q. [bs]lst. x = [q \ bs]lst. (q \ x) \ q \ bs = p \ bs" using Abs_rename_lst[OF a] by metis